2014
DOI: 10.1017/s0022215113003411
|View full text |Cite
|
Sign up to set email alerts
|

Suction diathermy adenoidectomy performed in the district general hospital

Abstract: Given the rare but serious potential complications, the authors support National Institute for Health and Clinical Excellence guidance, which recommends that only surgeons with specific training perform this technique. By using the standard procedures for clinical governance, it is possible to ensure safe practice of even little-used techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…No evidence of nasopharyngeal stenosis and scarring was seen in the majority of studies with suction electrocautery technique. [59,63] Some studies have suggested an increase in pain and complication rates but a meta-analysis did not confirm those results. [63] Casserly et al [64] studied bacteremia during adenoidectomy.…”
Section: Adenoidectomy Indicationsmentioning
confidence: 95%
See 1 more Smart Citation
“…No evidence of nasopharyngeal stenosis and scarring was seen in the majority of studies with suction electrocautery technique. [59,63] Some studies have suggested an increase in pain and complication rates but a meta-analysis did not confirm those results. [63] Casserly et al [64] studied bacteremia during adenoidectomy.…”
Section: Adenoidectomy Indicationsmentioning
confidence: 95%
“…[58] The National Institute for Health and Clinical Excellence (NICE) guidelines suggested that this technique should be performed by specifically trained surgeons. [59,60] However, a study on preferred tonsillectomy and adenoidectomy methods among the members of the American Society of Pediatric Otolaryngology (ASPO) suggested that electrocautery adenoidectomy (ECA) was the most common method used for adenoidectomy. [61] An electrical current is applied from the suction cautery to the adenoid tissue to liquefy and ablate it under indirect/direct visualization with a laryngeal mirror.…”
Section: Adenoidectomy Indicationsmentioning
confidence: 99%
“…The rate of regrowth or recurrence of adenoid is significantly lower in suction diathermy adenoidectomy compared to curette adenoidectomy. 9,10 Another complication of the procedure is pharyngeal infection. Some patients experience a bad odor after the procedure.…”
Section: Discussionmentioning
confidence: 99%